ABU MANSUR AL-MOTURIDI IS THE KING OF KALAM PHILOSOPHY - Adashova Maxsuma Mahmudboevna (Galaxy International Interdisciplinary Research Journal, 2021)
This article contains examples of the respect shown by scholars to the great figure of the Sultan of theology, Sheikh Abu Mansur al-Moturidi and his great services in the path of science.